How relationship quality, autonomous work motivation and socialization experience influence the adjustment of self-initiated expatriates in China. Issue 2 (30th March 2021) - Jannesari, Milad T.; Sullivan, Sherry E.
Abstract : Purpose: The continued expansion of organizations outside China's planned economy due to the Belt-and-Road Initiative (BRI) is expected to increase recruitment of self-initiated expatriates (SIEs). Drawing on social capital, motivation and socialization theories, this study examines the experiences of SIEs in China, which is considered one of the most difficult locations for foreigners to work. While previous research has focused on the impact of individual characteristics on adjustment, this study explores the interplay among relationship quality (trust and shared vision), autonomous work motivation, socialization experience and adjustment. Design/methodology/approach: Based on the developed theoretical framework, hypotheses are proposed and tested using data collected by surveying 274 SIEs in China. Findings: Relationship quality with host country nationals (HCNs) was positively associated with adjustment, and autonomous work motivation fully mediated this relationship. Socialization experience moderated the association between relationship quality and autonomous work motivation. Specifically, SIEs' socialization experience strengthened the associations of trust and shared vision with autonomous work motivation. However, socialization experiences failed to moderate the mediated effects of trust and shared vision on adjustment via autonomous work motivation. Originality/value: This study answers repeated calls for more research on SIEs' adjustment and SIEs working in non-Western countries, especially China. The findings underscore the importance of studying SIE-HCN work relationships and the theoretical value of autonomous work motivation as an underlying mechanism by which the quality of an SIE's relationship with an HCN colleague influences adjustment.